(untitled) (Research, Society and Development, 2020)
This study aimed to compare the fertigation method with direct manual application and with foliar application in concentrations of 0%, 10%, 15%, 30% and 50%, to identify the most appropriate management system for the use of biofertilizer produced from manipueira based on the physiology of Vigna unguiculata (L.) Walp during the development of the crop, in order to mitigate environmental contamination caused by inadequate disposal of effluent generated in the production of cassava flour in the municipality of Paragominas-PA. In the physical evaluation, after the experiment, it was found that the highest concentrations (15%, 30% and 50%), hindered the vegetative development of beans and soil infiltration, a consequence of the salinization process. However, although no plant reached the reproductive phase within the 90 days indicated in the literature, the biofertilizer proved to be efficient in the concentration of 10% of manipueira in direct application, where it achieved better germination results, with more beans completing the V4 phase (emergence of a third trifoliate leaf with expanded leaflets), including in relation to individuals in the control area (without fertigation treatment).